PyTherNal: A python program for analyzing curie temperature from thermomagnetic data - Nanlohy, George Billy; Yosia, Gabrian Granito; Salim, Christopher; Mariyanto, Mariyanto (Journal of physics. Conference series, 2022)
Thermomagnetic analysis is performed by bringing subject materials into its cooled and heated state, followed by analyzing the magnetic moment change. Performing these would result in obtaining the Curie Temperature of the materials, which is essential in estimating magnetic minerals contained in material samples. PyTherNal (Python Thermomagnetic Analyzer) is a thermomagnetic analysis tool in Python environment meant to assist in analyzing thermomagnetic data. The advantages of Python in its functionality and flexibility of being used in any operating system (OS) became the main reason for the program to be written in Python. PyTherNal is designed to assist in estimating Curie temperature of materials through thermomagnetic method, by locating the maximum curvature of the highest value of second (2 nd ) derivative of both cooling and heating data. To facilitate these, PyTherNal generates three figures, which are the curves for the thermomagnetic data, its 1 st derivative, and its 2 nd derivative. An advantage of the program is that it performs smoothing to increase the accuracy in estimating the Curie temperature as doing so would significantly minimize the variability of the derivative curve. Since the program is written in Python, it is open-source and therefore free to use. It is also capable of cross-platforming.